PSYCHO-EMOTIONAL CHANGES IN PATIENTS WITH CHRONIC HEART FAILURE - Matskevich, S. A.; Barbuk, O. A.; Belskaya, M. I.; Zharankov, K. S. (Evrazijskij kardiologičeskij žurnal (Online), 2016)
Objectives. To define the presence and severity of anxiety and depression stress and assess the impact produced on the life quality in subjects with CHF secondary to registered macrofocal (Q wave) myocardial infarction in medical history. Material and methods. General clinical examinations, psychological testing. Results. A total of 118 patients with II, III FC NYHA chronic heart failure were examined. Anxiety and depression events were defined in 46.6% of cases. As heart failure progresses, anxiety and depression symptoms increase, with the prevalence of anxiety in the presence of FC II and depression in the presence of FC III. Life quality in patients with concomitant anxiety and depression stress is significantly worse compared to patients with normal psychoemotional state. Conclusion. Thus, individuals with CHF showed psychoemotional changes including anxiety and depression stress, which may adversely affect CHF course. Anxiety and depression symptoms increase as heart failure progresses.